Albendazole-lipid nanocapsules: Optimization, characterization and chemoprophylactic efficacy in mice infected with Echinococcus granulosus - Ullio Gamboa, Gabriela Veronica (2019)
Cystic echinococcosis (CE), which is caused during the metacestode larval stage of Echinococcus granulosus, is a life-threatening disease and is very difficult to treat. At present, the FDA-approved antihelmintic drugs are mebendazole (MBZ), albendazole (ABZ) and its principal metabolite ABZ sulfoxide (ABZSO), but as these have a therapeutic efficacy over 50%, underlining the need for new drug delivery systems. The aim of this work was the optimization and characterization of previously developed ABZ lipid nanocapsules (ABZ-LNCs) and evaluate their efficacy in mice infected with E. granulosus. LNCs were prepared by the phase inversion technique and characterized in terms of size, surface charge, drug loading, and in vitro stability followed by an in vivo proof-of-concept using a murine model infected with E. granulosus. Stable particle dispersions with a narrow size distribution and high efficiency of encapsulation (≥90%) were obtained. ABZ-LNCs showed a greater chemoprophylactic efficacy than ABZ suspension administered by the oral route as 4 out of the 10 ABZ-LNCs treated mice did not develop any cysts, whereas the infection progressed in all mice from the ABZ suspension group. Regarding the ultrastructural studies of cysts, mice treated with ABZ-LNCs or ABZ suspension revealed changes in the germinal layer. However, the extent of the damage appeared to be greater after ABZ-LNC administration compared to the suspension treatment. These results suggest that ABZ-LNCs could be a promising novel candidate for ABZ delivery to treat CE.